Odpowiedzi

2010-04-09T15:27:31+02:00
B-6= -8 /+6
b= -2


d-(-9)= -21
d+9 = -21 /-9
d= -30


x* (-1)= -8
-x = -8 /*(-1)
x= 8



y* (-8)=5
-8y = 5 /:8
-y = 5/8 /*(-1)
y= -5/8


z/10= -1 /*10
z= -10
2010-04-09T15:29:02+02:00
B-6= -8 b=?
b-6=-8
b=-8+6
b=-2

d-(-9)=-21
d=-21+9
d=-30

x*(-1)=-8
-x=-8
x=8

y*(-8)=5
-8y=5
y=5/-8

z/10=-1
z=10*(-1)
z=-10
2010-04-09T15:29:18+02:00
B-6=-8
b=-8+6
b=-2

d-(-9)=-21
d+9=-21
d=-21-9
d=-30

x*(-1)=-8
-x=-8/*(-1)
x=8

y*(-8)=5
-8y=5/:(-8)
y=-5/8

z/10=-1/*10
z=-10